Peran Majelis Taklim Anwarul Mahabbah dalam Membentuk Karakter Religius Remaja - Rizkiyah, Fifin Naili; Widad Ainah (Afkaruna: International Journal of Islamic Studies (AIJIS), 2023)
Majelis Taklim "Anwarul Mahabbah" makes teenagers as target of da'wah because their low religious character in this era of globalization. By instilling religious values in the activities of Majelis Taklim, teenagers are expected to grow into individuals who have religious characters. This study aims at determining the role of Majelis Taklim "Anwarul Mahabbah" in shaping religious character of teenagers in Sempaja Utara. The research is descriptive qualitative with instruments used are interviews and observation. The results of this study indicate that Majelis Taklim "Anwarul Mahabbah" plays very important roles in shaping teenagers’ religious characters. Some of ilahiyah characters they have are carrying out the obligations of five daily prayers and Ramadan fasting, reading the Holy Qur'an regularly, leaving immorality such as drunkenness and ngelem, filial piety towards parents, and increasing understanding fiqh and akhlak. The insaniyah characters also grow from the mutual cooperation when joining the routines activities and celebrating Islamic holidays. In addition, teenagers become more polite and respectful to teachers and elders